(3GdbhGYO GdEdgjI aj GdcdGe hGdMceIs - (3GdHMQGfj, ceGd GdOjf, gjKe Hf Ydj Hf gjKe, J (B679(3g`s ((3UGdM Hf jhSas)
(3ChdgG (B:s
(3hGdeSdejf CHh GdeXaQ YHO GdYRjR Hf LYaQ (B... (3Cf CcJH dg eNJUQG (B... (3jLeY Hjf JMbjb GdeSGFd(B... (3hajg eHGMK, GdHMK GdChd MUhd UhQI GdTjA aj GdYbds
(3BNQgG (B:s
(3GdKGdK(B: (3dGJaGb HjffG hHjf GdNUe Ydi MjGI GdMVQ hEdjGS YdjgG GdSdGe ef GdfHjGA hGdSajGfj hGdOLGd ef GdCTbjGA(B... (3hGdMeO ddg Mb MeOg(B...s
(3JHUQI GdYfhGf (B:s
(3GdbhGYO GdEdgjIs
(3JHUQI GdeDda (B:s
(3hjbGd aj GSeg(B: (3ejKe Hf Ydj Hf ejKes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI Qbe(B: 940s
Keywords: (3GdJhMjO hGdedd hGdfMds